Effect of Profitability and Leverage on Disclosure of Corporate Social Responsibility in Islamic Commercial Banks - Alfiyah, Siti Nur (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
The purpose of this study is to determine the effect of profitability and leverage on Corporate Social Responsibility. The population in this study are all Sharia Commercial Banks registered in the Financial Services Authority from 2014-2016. The sampling technique used purposive sampling method and obtained 10 research samples. For the dependent variable (y) of this research is Corporate Social Responsibility. For independent variable (x) that is profitability and leverage. The method used is quantitative research method. For data source is secondary data by using data analysis with statistic used SPSS software program assistance Smart SPSS 20. The results of this study indicate that profitability has no significant effect on Corporate Social Responsibility. The study also concluded that Leverage significantly influence Corporate Social Responsibility.